(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the research Karnad’s plays, meticulously dissecting the layers of mythology and symbolism that underlie them. Karnad’s remarkable talent for seamlessly integrating traditional Indian mythological elements with contemporary themes is meticulously examined, revealing the profound cultural and historical significance of his plays. Each major work by Karnad is analyzed in detail, uncovering the symbolic motifs and archetypal characters that populate his theatrical universe. the abstract underscores the book’s significance as an essential resource for scholars, students, and enthusiasts of Indian theatre and literature. It not only elucidates the importance of myth and symbolism in Karnad’s plays but also situates them within the broader context of Indian drama and the global theatrical landscape. The book’s accessible and engaging narrative style ensures its accessibility to a diverse readership, making it an indispensable addition to the study of contemporary Indian theatre.